Entwicklung metropolitaner Funktionen im polyzentralen deutschen Städtesystem – Raummuster der Konzentration und funktionalen Spezialisierung - Volgmann, Kati (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The importance of big cities and metropolises is related to the structural change in favor of the service- and knowledge economy and global economic interrelations, which generate strategic locations or nodes with control and management functions. These high-quality functions are concentrated at these nodes, which are distinct from other spatial areas. Subject of the paper is a theoretical systematization and operationalization of such metropolitan functions which based on international urban concepts and the typology of metropolitan functions—decision and control function, innovation and competition function, gateway function and symbolic function. For this purpose a database of 48 indicators is created that refers to localized functional attribute characteristics to determine the degree of Metropolität of all 439 urban counties and functional-analytical metropolitan areas. It is to be analyzed which cities have metropolitan functions, and how these developed with regard to processes of spatial concentration and functional specialization between 1995 and 2010. It is assumed that due to agglomeration economies (e.g. spatial proximity between actors or developmental edge) the “big” metropolitan areas are the winner of the processes of metropolisation.